Visual Search in Naturalistic Scenes Reveals Impaired Cognitive Processing Speed in Multiple Sclerosis - Gehrig, Johannes; Bergmann, Heinrich Johannes; Fadai, Laura; Soydaş, Dilara; Buschenlange, Christian; Naumer, Marcus J.; Kaiser, Jochen; Frisch, Stefan; Behrens, Marion; Foerch, Christian; Yalachkov, Yavor (Frontiers in Neurology, 2022)
Background Standardized neuropsychological testing serves to quantify cognitive impairment in multiple sclerosis (MS) patients. However, the exact mechanism underlying the translation of cognitive dysfunction into difficulties in everyday tasks has remained unclear. To answer this question we tested if MS patients with intact versus impaired information processing speed measured by the Symbol Digit Modalities Test (SDMT) differ in their visual search behavior during ecologically valid tasks reflecting everyday activities. Methods Forty-three patients with relapsing-remitting MS enrolled in an eye-tracking experiment consisting of a visual search task with naturalistic images. Patients were grouped into “impaired” and “unimpaired” according to their SDMT performance. Reaction time, accuracy and eye-tracking parameters were measured. Results The groups did not differ regarding age, gender and visual acuity. Patients with impaired SDMT (cut-off SDMT-z-score < -1.5) performance needed more time to find and fixate the target: p=0.001, q=0.006). They spent less time fixating the target (p=0.014, q=0.042). Impaired patients had slower reaction times (p=0.027, q=0.0495) and were less accurate, independent of the patients' upper extremity function. Conclusion Dysfunctional visual search behavior may be one of the mechanisms translating cognitive deficits into difficulties in everyday tasks in MS patients.